Pengaruh Faktor Kepuasan Kerja Terhadap Kinerja Karyawan Pada Kantor PT Permata Finance Indonesia Cabang Makassar - Finta Luka; Agung Widhi Kurniawan; Burhanuddin Burhanuddin; Siti Hasbiah; Tenri S.P. Dipoatmodjo (FEB Universitas Sultan Ageng Tirtayasa, 2023)
This study aims to determine the effect of job satisfaction factors both partially and simultaneously on employee performance at the office of PT Permata Finance Indonesia Makassar Branch, and to determine which job satisfaction factors have a greater influence on employee performance. The independent variable in this study is the job satisfaction factor which consists of the work itself, colleagues, rewards, and supervision, and the dependent variable is employee performance. The sample in this study were 31 respondents. This research is a quantitative study and was analyzed using multiple linear regression analysis using the data processing tool IBM SPSS Statistics 25 for Windows. The results of this study indicate that 1) The job satisfaction factor which consists of the work variable itself does not have a significant effect on employee performance, while the other three factors which consist of co-worker variables, rewards and supervision have a significant effect on employee performance. 2) Simultaneously the four independent variables have a significant effect on employee performance. 3) Reward is a factor of job satisfaction that has a greater influence on employee performance at the PT Permata Finance Indonesia Makassar Branch office.